Faktor Permintaan Non Fungsional Group Member terhadap Permintaan (Seri 1) - Iskandar Putong (Bina Nusantara University, 2010)
Non-functional analysis of demand factors on demand for group members are aimed to discover whether there is significant impact of non functional variable demand potential purchasing decision. 3 independent variable for the Snob Effect of X1, X2 for the bandwagon effect and X3 for the Veblen Effect and a dependent variable Y for Purchase Decision (Demand). The survey has 50 respondents and uses 21 item of a valid indicator. Analysis uses Pearson correlation model, Canonical Correlation and Hybrid intercorellation. The result of statistical analysis has proved the LOC by 95%, shows that there is significant impact between variable of X to Y in a different format (trade off or trade on). Multivariate Canonical Correlation showed that the effect of variable X to variable Y at 0,27%% whereas the effect of variable Y to variable X at 1%